Fetal and neonatal outcomes after term and preterm delivery following betamethasone administration in twin pregnancies. Issue 3 (September 2016) - Braun, Thorsten; Weichert, Alexander; Gil, Hannah C.; Sloboda, Deborah M.; Tutschek, Boris; Harder, Thomas; Dudenhausen, Joachim W.; Plagemann, Andreas; Henrich, Wolfgang
Abstract: Objective: To investigate effects of betamethasone on fetal growth and neonatal outcomes in twins. Methods: A retrospective cohort study was conducted of twins delivered at one center in Berlin, Germany, between 1993 and 2011. The betamethasone group included twin pregnancies with preterm labor, cervical shortening, preterm premature rupture of membranes, or vaginal bleeding, and exposure to betamethasone between 23 + 5 and 33 + 6 weeks. The control group included twin pregnancies with no betamethasone exposure matched for length at delivery. Fetal growth and neonatal anthropometric data were analyzed by twin‐pair structure, dose, and gestational age (linear mixed model). Results: Overall, 1922 live‐born twin pairs (653 betamethasone group, 1269 controls) were included. Compared with controls, late‐preterm twins exposed to betamethasone were lighter (mean difference –126 g), had a smaller head circumference (–0.4 cm), and a shorter body length (–0.8 cm) after adjustment for confounders ( P < 0.05). Female neonates from mixed or same‐sex twin pairs had a lower birth weight than controls (betamethasone ≤ 16 mg: –114 g; betamethasone 24 mg: –124 g; betamethasone > 24 mg: –187 g), with no detectable improvement in neonatal morbidity (hyperbilirubinemia, respiratory distress, asphyxia) or mortality. Conclusion: Betamethasone reduced birth weight, head circumference, and length of female preterm neonates in twin pairs in a dose‐dependent manner. The neonatal mortality and morbidity were not improved by betamethasone.